WANITA BERTATO: FAKTOR-FAKTOR YANG MEMPENGARUHI DAN MOTIVASINYA - Dewi, Sandra (EMPATHY Jurnal Fakultas Psikologi, 2013)
AbstractÂ Â This study is aimed to determine the factors that influence women to be tattooed and their motivation. Subjects in this study are two women who had more than one tattoo, for more than a year. The research method which is used was a qualitative research with phenomenological approach. The method of data collection is done by semi-structured interview combined with observation of the two subjects. To ensure the credibility of the data, conducted interviews was held with significant persons of subjects.The results of this study indicate that the factors that affect both tattooed subjects, among others: the fragile family relationships, social environment that can tolerate tattoo, and exposure to information about the tattoo. The study also reveals that the motivation for the subject I tattooed his body, that is, as the bond of interpersonal relationship with someone who is intimate, self-identity, a symbol of interests and hobbies, as well as the beauty aesthetically satisfying. While on the subject of motivation IIâs tattooed body, that is, as an identity, a symbol of interests and hobbies, as well as the beauty aesthetically satisfying. Also found motivation tattooed of body on both the subject of a media catharsis.Â Keywords: Factors that Affect, Motivation, Women, TattoosÂ Â